2018
DOI: 10.1080/01635581.2018.1460683
|View full text |Cite
|
Sign up to set email alerts
|

Antitumoral Potency by Immunomodulation of Chloroform Extract from Leaves of Nitraria retusa, Tunisian Medicinal Plant, via its Major Compounds β-sitosterol and Palmitic Acid in BALB/c Mice Bearing Induced Tumor

Abstract: This study evaluated the antitumoral effect of Chloroform extract from Nitraria retusa leaves, via its major compounds β-sitosterols and palmitic acid. BALB/c mice were subcutaneously inoculated with B16-F10 cells, then treated intra-peritoneally after 7 days with the chloroform extract for 21 days. They were then euthanized, and the tumors were weighed. Lung parenchyma was analyzed. Lymphocyte and macrophages proliferation, cytotoxic T lymphocyte (CTL) activities were evaluated using the MTT assay. Macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…They suggested that the protective action of N. retusa fruit extract could result from its content of the phenolic compounds. Boubaker et al (2018) indicated that treatment of tumor-induced mice with leaf extracts of N. retusa showed anti-tumor activity which was attributed to its most important components in the N. retusa, namely, palmitic acid and β-sitosterols (Boubaker, Chaabane, et al, 2015a;Boubaker, Mokdad Bzeouich, et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the protective action of N. retusa fruit extract could result from its content of the phenolic compounds. Boubaker et al (2018) indicated that treatment of tumor-induced mice with leaf extracts of N. retusa showed anti-tumor activity which was attributed to its most important components in the N. retusa, namely, palmitic acid and β-sitosterols (Boubaker, Chaabane, et al, 2015a;Boubaker, Mokdad Bzeouich, et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin has extensive biological properties, including antioxidant, anti-inflammatory, and antiapoptosis [ 27 , 28 ]. It has been shown that quercetin significantly increased the primordial follicle number and AMH level and decreased atretic follicle number in CTX-induced DOR mice [ 29 , 30 ]. β -Sitosterol is another significant bioactive compound.…”
Section: Discussionmentioning
confidence: 99%
“…β-sitosterol significantly hindered the expansion of transplantable tumors, protected lung parenchyma, and increased splenocyte proliferation and cytotoxic t lymphocyte activity in tumor-bearing mice, and enhanced host macrophage lysosomal activity, and antioxidant cellular activity, and inhibition of lipid peroxidation. The antitumor effect of β-sitosterol is related to its immunomodulatory activity ( Boubaker et al, 2018 ).…”
Section: Anti-tumor Mechanism Of Action Of the Active Ingredients Of ...mentioning
confidence: 99%